Analisis Perilaku Terhadap Es Teh Indonesia - Hudefah Hudefah; Fani Fardiani; Syamsul Hidayat (Jurnal Riset dan Inovasi Manajemen, 2024)
In the current digital era, product competitors are not only based on product quality but also on how their marketing position can be reached by many groups. This research aims to determine consumers' purchasing power towards Esteh Indonesia and how influential the flavor variants available at Esteh Indonesia are on consumer purchasing power. From the test results that have been determined, there is a reliable test result of 0.799, a normality test of 0.61 with a significance level of 0.05. So it can be concluded that consumer influence on Esteh Indonesia has a positive influence.